2014
DOI: 10.1373/clinchem.2014.229427
|View full text |Cite
|
Sign up to set email alerts
|

Association of 1,5-Anhydroglucitol with Diabetes and Microvascular Conditions

Abstract: Background 1,5-anhydroglucitol (1,5-AG) is inversely related to hyperglycemia and may be a useful indicator of short-term (1-2 week) hyperglycemia and glycemic excursions but its prognostic value is unclear. We sought to evaluate the associations of 1,5-AG with risk of diabetes and microvascular disease. Methods We measured 1,5-AG in blood samples from over 10,000 participants in the ARIC Study (baseline, 1990-1992) and characterized the independent associations with prevalent retinopathy, and with incident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 30 publications
4
53
1
1
Order By: Relevance
“…In those with diagnosed diabetes, those with the lowest levels of 1,5-AG (,6 mg/mL, representing the most GV) were 11 times more likely to have retinopathy compared with those with the highest levels of 1,5-AG (.10 mg/mL, representing the least GV). In those with diagnosed diabetes, low 1,5-AG was also associated with a greater than twofold increased risk of incident chronic kidney disease (21). These relationships for the entire study population are shown in Fig.…”
Section: Dwilliam T Cefalu Editor In Chief Diabetes Carementioning
confidence: 72%
See 1 more Smart Citation
“…In those with diagnosed diabetes, those with the lowest levels of 1,5-AG (,6 mg/mL, representing the most GV) were 11 times more likely to have retinopathy compared with those with the highest levels of 1,5-AG (.10 mg/mL, representing the least GV). In those with diagnosed diabetes, low 1,5-AG was also associated with a greater than twofold increased risk of incident chronic kidney disease (21). These relationships for the entire study population are shown in Fig.…”
Section: Dwilliam T Cefalu Editor In Chief Diabetes Carementioning
confidence: 72%
“…Another important supporting study was a recent publication reviewing the association of 1,5-anhydroglucitol (1,5-AG), a biomarker associated with GV, and outcomes in the Atherosclerosis Risk in Communities (ARIC) Study (21). 1,5-AG is a metabolically inert monosaccharide present in the diet.…”
Section: Dwilliam T Cefalu Editor In Chief Diabetes Carementioning
confidence: 99%
“…1,5-AG reflects glucose control over the previous 48 h to 2 weeks, its concentration is mainly useful in detecting postprandial glucose (PPG), where lower levels result from glucose peaks above the renal threshold and particularly useful in patients with A1C <8%. 49 1,5-AG was found to be negatively associated with longterm risk of microvascular outcomes, 14,50,51 and an increased risk of CV disease [52][53][54] and mortality in DM. 53 The concentrations of 1,5-AG decrease as pregnancy progresses in both nondiabetic and diabetic subjects 55 ; nonetheless, 1,5-AG has been found to be a useful marker in pregnancy complicated by DM, associated with mean glycemia, glycemic variability (GV), and glycemic exposure in females with T1D1 in whom glycemic control was assessed by a continuous glucose monitoring (CGM) system.…”
Section: Glycated Proteinsmentioning
confidence: 92%
“…Additional outcomes were determined through ARIC study surveillance using both annual telephone interviews and abstraction of hospitalization records, with follow-up until December 31, 2011. [35][36][37] Incident hypertension was assessed at each annual telephone interview as self-reported hypertension diagnosis or antihypertension medication use, or systolic BP $140 mmHg, diastolic BP $90 mmHg, or the use of antihypertension medications at a subsequent study visit. Incident diabetes was defined as self-reported diabetes diagnosis or use of diabetes medications during study visits or annual telephone interviews.…”
Section: Outcome Assessmentmentioning
confidence: 99%